Fear of Missing Out (FoMO) Causes Anxiety in Adolescents - Ayong Lianawati; Laily Dzihni Kharisma; Tri Prasetiyowati; Rizkah Intana Rahmah; Nur Syamsiyah; Mohammad Fajar Urifan; Anita Diasasari (Ma'soem University, 2023)
Fear of Missing Out (FoMO) is the fear of being left behind by new and interesting things that exist. Fear of Missing Out (FoMO) is not dangerous, but if handled properly, it can affect a person's emotional well-being or make individuals feel depressed, anxious, and dissatisfied with their lives, thus triggering stress and anxiety that can interfere with mental health. The research method used is quantitative, while the data collection method is done by distributing questionnaires to correspondents. Subjects or samples in this study amounted to 37 (thirty-seven) teenagers in Surabaya. This study uses a descriptive analysis method to determine the anxiety that occurs in adolescents due to Fear of Missing Out (FoMO). The questionnaire showed that adolescents who experienced FoMO were 8% of the total number of correspondents because they did not believe in their abilities and always saw others as better than themselves.